Development of food for an increasingly overweight population - FRANCO-AGUILAR, Alejandro; GRANDA-RESTREPO, Diana María; TORRES OQUENDO, Juan Diego (Vitae, 2018)
Nowadays, obesity is considered one of the biggest problems in public health, by its high prevalence and the relationship between the not chronic diseases such as diabetes, coronary heart disease, hypertension, dyslipidemia, among others. At the global level, over-weight is increased not only in high-income countries, but mainly in the low and medium, substantially in urban environments. In developing countries close to 35 million people were identified with this problem, while that developed the amount just reaches 8 million.